Tiny thoughts on honesty - Bezenac, Agnes; Bezenac, Agnes; Bezenac, Salem (Beirut Dar al Maaref bookshop, 2020)
suki experiences the negative feelings of stealing and reconizes the importance of honesty and gaining the trust of others
Education
For children from 3 to 6 years old
1
Keywords: Educational psychology